2011
DOI: 10.4049/jimmunol.1101578
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor α Signaling in T Lymphocytes Is Required for Estradiol-Mediated Inhibition of Th1 and Th17 Cell Differentiation and Protection against Experimental Autoimmune Encephalomyelitis

Abstract: Estrogen treatment exerts a protective effect on experimental autoimmune encephalomyelitis (EAE) and is under clinical trial for multiple sclerosis therapy. Estrogens have been suspected to protect from CNS autoimmunity through their capacity to exert anti-inflammatory as well as neuroprotective effects. Despite the obvious impacts of estrogens on the pathophysiology of multiple sclerosis and EAE, the dominant cellular target that orchestrates the anti-inflammatory effect of 17β-estradiol (E2) in EAE is still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
143
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(148 citation statements)
references
References 50 publications
(81 reference statements)
3
143
0
2
Order By: Relevance
“…The differentiation of the Th17 subset of CD4þ cells is inhibited by estrogen via a direct effect mediated by ERa (42). The specific contribution of Th17 in ovx induced bone loss remains controversial as one study reported that IL-17R null mice are more susceptible to ovx induced bone loss than controls (43), while another group found mice lacking IL-17R and mice treated with anti IL-17 antibody to be protected against ovx induced bone loss (44).…”
Section: T Cells Mediate the Effects Of Estrogen Deficiency In Bonementioning
confidence: 98%
“…The differentiation of the Th17 subset of CD4þ cells is inhibited by estrogen via a direct effect mediated by ERa (42). The specific contribution of Th17 in ovx induced bone loss remains controversial as one study reported that IL-17R null mice are more susceptible to ovx induced bone loss than controls (43), while another group found mice lacking IL-17R and mice treated with anti IL-17 antibody to be protected against ovx induced bone loss (44).…”
Section: T Cells Mediate the Effects Of Estrogen Deficiency In Bonementioning
confidence: 98%
“…Estrogen effects are mediated by estrogen receptors (ERs) ERa and ERb, which function as ligand-induced transcription factors (3). This regulatory action of estrogens on immune responses and autoimmunity are thought to be due to a direct action on immunocompetent cells of the innate and adaptive immune systems (4), which have been recently shown to functionally express ERs, particularly ERa (5)(6)(7)(8)(9)(10)(11). Alternatively, estrogens, through their ERs, may act on precursor cells to regulate the differentiation and functions of lymphoid and myeloid cells (12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Estrogeninduced EAE protection is mediated by upregulated PD-1 expression within the Treg-cell compartment, which reduces peripheral IL-17 production (9). Lelu et al demonstrated that hematopoietic cell ERα expression is critical for mediating E2s inhibitory effect on Th1 and Th17 cell priming, which results in EAE protection (8). However, to our knowledge, there have been no publications regarding the effect of ERα on IL-23 in EAE.…”
Section: Discussionmentioning
confidence: 84%
“…Secondly, certain studies have reported estrogen-mediated protection against EAE in regulatory B cells and the mediation of MMP-9 activity through ERα (10,23). Thirdly, Lelu et al demonstrated that ERα expression is critical in hematopoietic, but not endothelial cells; it mediates the estrogen inhibitory effect on Th1 and Th17 cell priming, which protects against EAE (8). Finally, reactive astrocytes are a target of the inhibitory action of nuclear ERα on chemokine expression; this observation suggests that targeting astrocytic nuclear factor-κB may be a useful therapeutic goal (15,24).…”
Section: Foxp3mentioning
confidence: 99%
See 1 more Smart Citation